Let's solve for x.<span><span><span><span>3x</span>y</span>−<span>2x</span></span>=17 </span>Factor out variable x.<span><span>x<span>(<span><span>3y</span>−2</span>)</span></span>=17</span> Divide both sides by 3y-2.<span><span><span>x<span>(<span><span>3y</span>−2</span>)</span></span><span><span>3y</span>−2</span></span>=<span>17<span><span>3y</span>−2</span></span></span><span>x=<span>17<span><span>3y</span>−2</span></span></span>Answer:<span>x=<span>17<span><span>3y</span>−<span>2 </span></span></span></span>